The lonely otter a heart-warming story about love and friendship - Wilson , Clare Victoria; Price, Holly (London, New York, NY Dorling Kindersly Limited ; DK Publishing, 2023)
"Valentine's Day is near, but Otto the otter feels as lonely as ever! He would love a friend to play with, but this can be quite scary when you're shy. When he spots another otter who is always on her own, he thinks he's found someone just like him... Will this lonely otter pluck up the courage to discover if she is his perfect match?"-- Page 4 of cover
English Stories
Keywords: Friendship Fiction; Picture books